A Survey of Reading Requirements in Physics Education Journals for Undergraduate Students - Marsa Khoerunnisa; Nina Widiya Nengsih; Wahyunengsih (Jurnal Pendidikan dan Ilmu Fisika, 2025)
This study investigates the reading needs and difficulties of Indonesian undergraduate Physics Education students when engaging with English-language physics education journals. Using a descriptive quantitative survey design, data were collected from 52 students through a semi-standardized 40-item Likert questionnaire (1–5) covering eight dimensions: reading purposes, awareness of journal structure, vocabulary and technical terms, comprehension skills, reading strategies, reading difficulties, attitudes and motivation, and institutional support. Content validity was confirmed through expert judgment, and internal consistency was excellent (Cronbach’s alpha = 0.956). Descriptive analysis in Google Sheets showed that students strongly value journal reading for coursework, thesis writing, and professional preparation, and they demonstrate basic familiarity with IMRAD conventions. However, they still experience major barriers in understanding discipline-specific and methodological vocabulary, interpreting multimodal data such as tables, graphs, and diagrams, and navigating Result sections when journal layouts vary. Strategy use also remains limited, as students tend to read linearly and rely on translation tools rather than using abstract-first reading, skimming, or scanning consistently. Although motivation toward journal reading is positive, low confidence in reading without translation indicates that skills development has not matched their academic awareness. The study highlights the need for integrated journal-reading support in Physics Education programs, especially systematic vocabulary enrichment, guided multimodal-reading practice, and flexible strategy training, supported by stronger institutional access to international journals.